2022
DOI: 10.1101/2022.12.01.518701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The oncogenic fusion protein TAZ-CAMTA1 promotes genomic instability and senescence through hypertranscription

Abstract: TAZ-CAMTA1 is a fusion protein found in over 90% of Epithelioid Hemangioendothelioma (EHE), a rare vascular sarcoma with an unpredictable disease course. To date, how TAZ-CAMTA1 initiates tumour formation remains unexplained. To study the oncogenic mechanism leading to EHE initiation, we developed a model system whereby TAZ-CAMTA1 expression is induced by doxycycline in primary endothelial cells. Using this model, we establish that upon TAZ-CAMTA1 expression endothelial cells rapidly enter a hypertranscription… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…Here, RNA-sequencing confirmed that TC or YT mediates a transcriptional programme similar, but not identical, to the activated TAZ/YAP mutants TAZ4SA and YAP5SA [10]. This is in agreement with transcriptomic studies using alternative EHE model systems [11,38,39,[61][62][63].…”
Section: Cell Line-based Modelssupporting
confidence: 87%
See 2 more Smart Citations
“…Here, RNA-sequencing confirmed that TC or YT mediates a transcriptional programme similar, but not identical, to the activated TAZ/YAP mutants TAZ4SA and YAP5SA [10]. This is in agreement with transcriptomic studies using alternative EHE model systems [11,38,39,[61][62][63].…”
Section: Cell Line-based Modelssupporting
confidence: 87%
“…In recent years, a range of model systems for investigating EHE have been reported, and together have greatly improved our understanding of the disease [10,38,39,[60][61][62][63]. These include in vitro and in vivo systems established using different approaches (Table 1).…”
Section: Ehe Model Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their dysregulation or inhibition can wreak havoc, influencing a plethora of crucial pathways and mechanisms. These include DNA damage triggered by hypertranscription or via ATM-P53 axis, arrest in G1 and S-phase of the cell cycle, HR and NHEJ defects due to the suppression of BRCA1-RAD51 and HDAC1 activation, instigating T-cell acute lymphoblastic leukemia by modifying the NOTCH1, PTEN-PI3K-AKT, and MYC pathways, curtailing platelet function by impacting cyclic nucleotide pathways, undermining hemostasis by inhibiting platelet clumping through the reduction in αIIbβ3 expression, obstructing DNA replication due to changes in the RBBP6/ZBTB38/MCM10 axis, and imbalancing the proliferation-to-apoptosis ratio of lymphocytes, among others [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a significant portion of the genes implicated in fusion events (Table 1) play roles in preserving genomic stability. These include CAMTA1 [9], ESCO1 [10,11], FOXO3 [12][13][14], GOLGB1 [15], MAP7 [16], REV3L [17], RRM2B [18], USP38 [19], VIM [20], and ZBTB38 [21]. They are involved in DNA replication, ensuring accurate genetic material duplication, and DNA repair mechanisms that fix damage.…”
Section: Genes Engaged In Fusion Events Predominantly Govern Genomic ...mentioning
confidence: 99%